Investigation of the Possibility to Implement a Heat Pump for the Recovery of Heat From Process Cooling Water - Ekenberg,Ida; Söderberg,Ida (2024)
This report aims to investigate the possibilities to implement a high temperature heat pump at a Dow facility in Landskrona. By implementing a heat pump, waste heat from the production can be recovered and reused in the process. The question at issue is whether there will be enough energy available when needed due to an intermittent process, and if a heat pump will be feasible to implement. To investigate the possibilities, the energy availability in the different parts of the process was determined. A simulation of a heat pump for the process could then be executed in Aspen Plus. Furthermore, the intermittency was analyzed as well as the feasibility. The heat pump market was analyzed and different options of for example refrigerants were discussed. From the simulations, it was concluded that a heat pump of approximately 0.46 MW in heating and 0.31 MW in cooling capacity is best suited for this process, and will create the needed hot process water as well as cool off the cooling water. Ammonia was chosen as the best refrigerant option due to a suitable temperature interval and small environmental impacts. It is determined that a heat pump can be adapted to the intermittency since storing of hot process water is possible. For a heat pump unit with the heating capacity of 218 kW recommended by a company, the investment could possibly be feasible on a 3.5 year payback period, but this is only if the facility can increase the yearly production on account of the heat pump and thus increase the ROI. With these conclusions, there is a need for further investigation and evaluation of especially the intermittency and possibilities to shorten the production times to increase the profitability.
Keywords: chemical engineering; heat pumps; heat recovery; process design